'Uneven consequences' of international English-medium-instruction programmes in China: a critical epistemological perspective. Issue 4 (21st April 2021) - Song, Yang
ABSTRACT: Critical studies on internationalisation of higher education (IHE) have addressed the uneven global geopolitics of knowledge production as reinforced and reproduced through policy making and mechanism of professional organisations. Yet it remains unknown about the dynamics of epistemic exchanges in between agents at multiple dimensions of IHE, particularly in Asian contexts. Adopting a critical epistemological perspective [Chen, K.-H. 2010. Asia as Method: Toward Deimperialization . Durham, NC: Duke University Press], the present study examines international and Chinese students' epistemic practices in mixed English-Medium-Instruction (EMI) Master's degree programmes in a top-ranked comprehensive university in Shanghai, China. The in-depth student/instructor interviews and ethnographic classroom observation converge to reveal that the EMI curriculum constructs an implicit hegemonic hierarchy among students based on their pre-enrolment possessions of linguistic capital of English and cultural capital concerning Americanised academic norms and discipline-specific knowledge. Given the implicit hegemony, it is also argued that students have developed varied degrees of epistemic awareness and resorted to strategies of inter-referencing and cultural syncretism in order to negotiate diverse epistemic frames of reference with regards (1) English as an academic lingua franca, (2) the epistemic domination of the Global North, and (3) reimagining China and modernity. Practical and conceptual implications on IHE are proposed based on the analysis.